Layer number controllability of transition-metal dichalcogenides and the establishment of hetero-structures by using sulfurization of thin transition metal films. (11th January 2017) - Chen, Kuan-Chao; Chu, Tung-Wei; Wu, Chong-Rong; Lee, Si-Chen; Lin, Shih-Yen
Abstract: Large-area and uniform MoS2 films are fabricated by using sulfurization of pre-deposited molybdenum (Mo) films. One- and three-layer MoS2 films are obtained by sulfurizing 0.5 and 1.0 nm Mo films, respectively. The results have demonstrated the good layer number controllability of this growth technique down to single-layer MoS2 . By sequential sulfurization of 0.5 nm W, 0.5 nm Mo and 0.5 nm W under the same condition, three layers of the WS2 /MoS2 /WS2 hetero-structure are established, which has demonstrated the potential of this growth technique for the establishment of 2D crystal hetero-structures.